MENEGASKAN KEMBALI KEBERADAAN KLAUSULA BAKU DALAM PERJANJIAN - Ginting, Miko Susanto (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
Inclusion of standardized clause in contract should not be denied often done by reason of effectiveness and efficiency in the transaction. The existence of standardized clause based on approval towards contract so that applies as a Law for the parties. However, at the other side, there are arguments who opposed inclusion of the standardized clause in contract, especially based on the balance and fairness principles in contract. By using descriptive analytical method and juridical normative approach, I am trying to answer validity or invalidity of standardized clause in contract. In addition, also elaborated some decisions of the court in considering and deciding the standardized clause in contract. In the end, either scholar’s opinions or court decisions was still quite varied in viewing inclusion of standardized clause in contract. Nevertheless, toward that difference view already tried to find the meeting point through Law No. 8/1999 on Consumer Protection, where the standardized clause inclusion in contract is not prohibited, along do not contain substance or shape contrary with the Law. Keywords: standardized clause, agreement, balance in contract.